Village Spatial Planning Based on Its Potential as Guidelines for Guided and Sustainable Village Development - Mustika Kusumaning Wardhani; Bambang Setioko; Edward Endrianto Pandelaki (TATALOKA, 2021)
Historical areas that support tourism activities will always adapt to match the complexity of tourism needs in the last few decades. The uniqueness of Kotagede is that there are traditional settlements of silver craftsmen's (Javanese: Abdi Dalem Kriya). The history of silver craftsmen's settlement has been formed since the Dutch colonial era and has survived until now as a characteristic of Kotagede. Silver craftsmen in Kotagede have a dilemma to survive for SMEs home-based or adapt to sell products to a larger scale industry. The research objectives are to determine whether or not there is a change in the settlement function caused by the silver home-based industry activities and to what extent the change has occurred. The method used is a quantitative method with a positivistic paradigm and uses descriptive analysis for data interpretation. Statistical data analysis used multivariate linear regression (SPSS V26). In this study, it was found that there was an effect of Silver home-based Industry Activities on change in residential space function with the low significance of 25.6 % while 74.4 % was thought to be influenced by other activities outside the research model. Partially, the highest variable effect on settlement changes is production activities that can be found in Purbayan and Prenggan Village. With the low significant impact results on settlement changes, It is hoped that the silver production activities (home-based industry) have the potential to be promoted as part of the survivability concept of tourism in Kotagede by advancing SMEs itself.